Analysis of N6-Methyladenosine Methyltransferase Reveals METTL14 and ZC3H13 as Tumor Suppressor Genes in Breast Cancer - Gong, Peng-Ju; Shao, You-Cheng; Yang, Yan; Song, Wen-Jing; He, Xin; Zeng, Yi-Fan; Huang, Si-Rui; Wei, Lei; Zhang, Jing-Wei (Frontiers in Oncology, 2020)
Objectives Recently, an increasing number of studies have revealed that N6-methyladenosine (m6A) functions as a significant post-transcriptional modification which plays a critical role in the occurrence and progression of enriched tumors by regulating coding and non-coding RNA biogenesis. However, the biological function of m6A in breast cancer remains largely unclear. Materials and Methods In this study, we used a series of bioinformatic databases and tools to jointly analyze the expression of m6A methylation transferases (METTL3, METTL14, WTAP, RBM15, RBM15B and ZC3H13) and investigate the prognostic value of METTL14 and ZC3H13 in breast cancer. Besides, we analyzed the downstream carcinogenic molecular mechanisms related to METTL14 and ZC3H13 and their relationship with immune infiltration in breast tumor tissues. Results The results showed that METTL14 and ZC3H13 were the down-regulated m6A methylation transferases in breast cancer. Survival outcome analysis suggested that abnormally low expression of METTL14 and ZC3H13 could predict unfavorable prognosis in four breast cancer subtypes. Moreover, their down-regulation was associated with ER-, PR- and triple-negative breast cancer patients, as well as tumor progression (increased Scarff, Bloom and Richardson grade status and Nottingham Prognostic Index classification). Co-expression analysis revealed that METTL14 and ZC3H13 had a strong positive correlation with APC, an antagonist of the Wnt signaling pathway, indicating they might cooperate in regulating proliferation, invasion, and metastasis of tumor cells. METTL14, ZC3H13, and APC expression levels had significant positive correlation with infiltrating levels of CD4+ T cells, CD8+ T cells, neutrophils, macrophages, and dendritic cells, and negative correlation with Treg cells in breast cancer. Conclusions This study demonstrated that down-regulation of METTL14 and ZC3H13 which act as two tumor suppressor genes was found in breast cancer and predicted poor prognosis. Their abnormal expression promoted breast cancer invasion by affecting pathways related to tumor progression and mediating immunosuppression.